THE WATER QUALITY AND FISH PRODUCTIVITY OF GOMBE ABBA RIVER - Kabiru Muhammad; Aishatu Bello Mahmoud; Bara’atu Abubakar; Sulaiman Mohammed (International Engineering Journal For Research & Development, 2020)
Water quality determine the productivity of the river in terms of fish species. At the moment, the fish diversity and its habitats management are great challenge due to difficulties in evaluating the effects of the habitat change. Fish population requires extensive surveying before and after any changes. This study aimed at basically determining the water quality and diversity of fish species in Gombe Abba river. The river was divided into four sites according to its size and characterized the water by determining the physicochemical parameters including pH, temperature, turbidity, dissolved oxygen (DO), electric conductivity and phosphate concentration. Fish species compositions of the four sites were studied over a period of four (4) months (June to September). The mean values of most of the physicochemical parameters were found to be within the acceptable range, while less phosphate concentration was discovered. Seven (7) species of fish belonging to five (5) families were discovered with Hydrocynus brevis being the most dominant species. The condition factor of the fish species identified showed a result of lower and higher condition. Four species had their K values greater than 2.0 (Hydrocynus brevis, Clarias gariepirzus, Labeo senegalensis and Hydrocynus vittatus), whereas, the remaining three had their condition factor greater than 1.0 (Hydrocynus forskahlii, Oreochromis nilolicus and Momyrus senegalensis). The calculated H value (Shannon wieners species richness) and J value (Pielou”s Index for species evenness) of the present study area were 1.862 and 0.309 respectively. The J value indicates that the fish species of Gombe Abba River is not evenly distributed. The calculated ‘Ma’ 6.06 (Margalef’s diversity index) for comparison of the sites showed variation depending upon the number of species.